The roles of human induced pluripotent stem cell-derived cardiomyocytes in drug discovery: managing in vitro safety study expectations. (2nd June 2020) - Gintant, Gary; Traebert, Martin
ABSTRACT: Introduction: Human induced pluripotent stem cell-derived cardiomyocyte (hiPSC-CM) preparations are increasingly employed in in vitro cardiac safety studies to support candidate drug selection and regulatory submissions. The value of hiPSC-CM-based approaches depends on their ability to recapitulate the cellular mechanisms responsible for cardiotoxicity as well as overall assay characteristics (thus defining model performance). Different expectations at different drug development stages define the utility of these human-derived models. Areas covered: Herein, the authors review the importance of understanding the functional characteristics of the evolving spectrum of simpler (2D) and more complex (co-cultures, 3D constructs, and engineered tissues) human-derived cardiac preparations, and how their performance may be evaluated based on analytical sensitivity, variability, and reproducibility in order to correctly match preparations with expectations of different safety assays. The need for consensus clinical examples of electrophysiologic, contractile, and structural cardiotoxicities essential for benchmarking human-derived models is also discussed. Expert opinion: It is helpful (but not essential) that hiPSC-CMs preparations fully recapitulate pharmacological responses of native adult human ventricular myocytes when evaluating cardiotoxicity in vitro . Further calibration and model standardization (aligning concordance with clinical findings) are necessary to understand the role of hiPSC-CMs in guiding cardiotoxicity assessments in early drug discovery efforts.